Khasayeva, Afaq - (:unkn) unknown (My University, 2026)
Afaq Shamil Khasayeva graduated with honors from the Faculty of English Language of the Azerbaijan Institute of Foreign Languages in 1987. Since then, she has been engaged in higher education, English language teaching, translation, and academic research. She has held academic and administrative positions at the Azerbaijan Polytechnic Institute, Baku Asia University, and Baku State University. Since 2016, she has been a Senior Lecturer at the Department of Foreign Languages of the Azerbaijan University of Architecture and Construction. Her research interests include English language teaching methodology, English for Academic Purposes (EAP), foreign language acquisition, intercultural communication, green education, and educational technologies. She is the author and co-author of 16 scientific and educational publications, including teaching aids, curriculum programmes, journal articles, and conference papers. She has completed international professional development programmes at the University of Leicester, Cambridge University (TKT), and the U.S. Department of State, and participated in academic mobility under the Orhun Exchange Programme (2024).